PENGARUH PENGUNGKAPAN SUSTAINABILITY REPORTING TERHADAP KINERJA KEUANGAN PERUSAHAAN PERTAMBANGAN - Rizqy Fadhlina Putri; Shita Tiara; Rini Fadhillah Putri (Universitas Dharmawangsa, 2023)
ABSTRACTÂ Analysis of the effect of sustainability report disclosure on financial performance using profitability ratios (ROA). The population in this study are mining companies that submitted sustainability reports using the GRI G4 standard between 2016 and 2020 and are listed on the Indonesia Stock Exchange. The object of this case study is a mining company that is traded on the Indonesian Stock Exchange. Nine organizations became the entire company sample for this study, which was conducted over five years. Multiple linear regression is used as a data analysis method. The research findings show that the economic, environmental, and social aspects of transparency all have a beneficial impact on a company's financial performance.Keywords: Sustainability Report (SR), Disclosure of Economic Aspects, Disclosure of Environmental Aspects, Disclosure of Social Aspects, Return On Assets (ROA)